2022
DOI: 10.1038/s41580-022-00460-3
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and directions in studying cell–cell communication by extracellular vesicles

Abstract: Cit a tio n fo r fin al p u blis h e d ve r sio n: v a n Ni el, G uill a u m e , C a r t er, D avid R. F., Cl ayt o n, Ale d, L a m b e r t, D a ni el W., R a p o s o, G r a ç a a n d Vad er, Pi e t e r 2 0 2 2. C h all e n g e s a n d di r e c tio n s in s t u dyi n g c ell-c ell c o m m u ni c a tio n by ex t r a c ell ul a r v e sicl e s. N a t u r e R evi e w s M ol e c ul a r C ell Biolo gy 2 3 ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
393
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 546 publications
(478 citation statements)
references
References 101 publications
(127 reference statements)
1
393
0
Order By: Relevance
“…EVs conform to a highly complex population demonstrated by high heterogeneity in size, biogenesis, origin, content, mechanism of action, and biological function. Indeed, their biogenesis, uptake by target cells and cargo delivery processes (endocytosis, trafficking to endo/lysosomes, membrane fusion, cargo release, and phenotypic changes in the recipient cell) are still unclear (please refer to the comprehensive review for detailed EV basic biology [ 13 ]). Mass spectrometry-based proteomics have shown that cargo selection mechanisms are highly regulated by post-translational modifications [ 14 ].…”
Section: Extracellular Vesicles: Current State and Emerging Conceptsmentioning
confidence: 99%
“…EVs conform to a highly complex population demonstrated by high heterogeneity in size, biogenesis, origin, content, mechanism of action, and biological function. Indeed, their biogenesis, uptake by target cells and cargo delivery processes (endocytosis, trafficking to endo/lysosomes, membrane fusion, cargo release, and phenotypic changes in the recipient cell) are still unclear (please refer to the comprehensive review for detailed EV basic biology [ 13 ]). Mass spectrometry-based proteomics have shown that cargo selection mechanisms are highly regulated by post-translational modifications [ 14 ].…”
Section: Extracellular Vesicles: Current State and Emerging Conceptsmentioning
confidence: 99%
“…These vesicles clearly have potential and may open new possibilities for precise medicine. However, many aspects of RBCEVs are still unclear such as how RBCEVs interact with other tissues and organs [ 120 ]; there are still challenges for their clinical translation. Therefore, research based on different disciplines is needed to realize the full potential of RBCEVs.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that they were all present as full-length in BDEVs, and therefore, have at least the potential to be translated in the recipient cells. However, studying the biological relevance of the mRNA content (and other RNA cargoes) in EVs and proving their functionality in the recipient cells is very challenging [ 68 , 69 ]. It has been shown in EVs of human glioblastoma stem cells that the number of mRNAs is substantially low, as it was estimated to be 1 copy in 1,000 EVs for the most abundant mRNA, and for others less than 1 copy every 10,000–100,000, or even 1 copy in a million EVs for some RNA species.…”
Section: Discussionmentioning
confidence: 99%